Government Policies on Small Scale Poultry Business and Environmental Health in Indonesia - Nyak Ilham (Indonesian Center for Animal Research and Development, 2015)
The government paid great attention to develop small-scale poultry business, to reduce poverty alleviation and increase employment opportunities. The government has established various policies to encourage the growth of poultry production cluster (PPC) in rural areas. However, the fact shows that these policies have not been able to solve the problems. Small-scale poultry business is particularly vulnerable to economic changes, including animal diseases. The economic crisis of 1997-1998 and avian influenza outbreaks in 2004-2006 had caused most of small-scale enterprises collapsed. Government policies to develop small scale poultry business which is environmental friendly are required so its existence does not disturb the public. Since 2006, the government has established various policies, ie. Village Poultry Farming (VPF) and compartment structuring. Based on evaluation and existing cases, the results have no meet the expectation yet, due to lack of sustain supervision. On the other hand, small scale poultry business has been set up on PPC’s under partnerships with companies. The government is expected to continue VPF program and should pay attention to the development of PPC that basically has been accepted by rural communities. Key words: Government policies, poultry, small scale, environmental health